INFLUENCER IMPACT; SOLUSI PRODUSEN DALAM MEMPROMOSIKAN PRODUK - Musthafa Syukur; Saida Salsabila (Jurnal Istiqro, 2022)
This study uses a qualitative approach in order to produce a description. This study aims to understand and analyze the strategy in promoting products using endorsements. In the development of technology for now, especially with the internet, it is very fast and has an impact on almost all areas of life, which for now is influenced by the internet. With the internet, it really provides opportunities for marketing or marketing is needed, the internet has an impact and the emergence of a digital advertising where business owners start using media as a promotional medium, because it can create opportunities for a company.